PROPOGANDA PERCEPATAN CALISTUNG (MEMBACA MENULIS BERHITUNG) BAGI ANAK USIA DINI DALAM PANDANGAN ORANGTUA - Ranti, Gemala; M, Mildha; A, Alfiana (EDUCHILD (Journal of Early Childhood Education), 2022)
The propaganda for the acceleration of Calistung has become a hot issue in the community, one of which is for parents in Watampone, South Sulawesi. The pros and cons illustrate that parents have different principles for their child's Calistung abilities. The practice of accelerating Calistung is carried out, with the hope that children have mature readiness before entering elementary school, without considering the stage of development and growth. This research method uses exploratory descriptive. The purpose of this study is to dig deeper into the views of parents in Watampone, South Sulawesi regarding the practice of Calistung given to early childhood. Data collection techniques used in-depth interviews, questionnaires, and observations to 30 parents with children aged 3-6 years. Based on the results, the percentage shows that 63,3% of parents in Watampone agree with the practice of accelerating Calistung, with the aim of making children run smoothly in Calistung. Then only 36,7% are against the Calistung acceleration, they really consider the readiness and stage of child development. These two views differ quite a lot, many parents in Watampone agree with the practice of accelerating Calistung. A small number of parents do not agree with the Calistung acceleration, because it considers the basic concepts of early childhood development, and chooses fun learning, namely learning while playing